Transport and storage properties of CrSi2/Si junctions made using the CAPVD technique - Menda, Ugur Deneb; Ozdemir, Orhan; Tatar, Beyhan; Urgen, Mustafa; Kutlu, Kubilay (ELSEVIER SCI LTD, 2010)
p-CrSi2/n-crystSi and p-CrSi2/p-crystSi hetero junctions produced by cathodic arc physical vapor deposition were worked out by means of capacitance-voltage-temperature (C-V-T) and current-voltage-temperature (I-V-T) measurements to investigate storage and transport properties. Former measurement on p-CrSi2/n-crystSi structure confirmed an abrupt type junction together with a building voltage at the proximity of 0.7 V. Though a fairly well rectification ratio (10(3) at +/- 2 V) was realized by I-V measurement, it became deteriorated with the increase in ambient temperature. From temperature dependence of I-V variations, distinct conduction mechanisms were identified. In forward (reverse) direction trap assisted single-multistep tunneling recombination (generation) and space-charge limited current flow that corresponded to low and high bias voltage regions, respectively, were identified. Moreover, an activation energy (E-A) determined from the slopes of I-V-T curves as 0.22 and 0.26 eV was interpreted as the energy position of a chromium-boron (Cr-B) complex-type point defect residing in n/p doped c-Si semiconductor in CrSi2/n-c-Si and CrSi2/p-c-Si junctions. The retrieved E-A was in agreement with the recent DLTS measurement. Based on the experimental observations, schematic current path was built to interpret I-V/C-V behaviors. The model was successful in explaining the decrease in measured capacitance under large forward bias voltage reported for the first time by us for the present CrSi2/Si junctions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Electrical properties; Current mechanisms; Activation energy; Cr-B complex; Chromium silicides; ELECTRICAL-TRANSPORT; SCHOTTKY STRUCTURES; FILMS; Engineering; Materials Science; Physics